AKIDAH AKHLAK LEARNING IN IMPLEMENTING CHARACTER EDUCATION IN MTs DARUL FALAH KETAPANG - Mutmainnah (IJGIE (International Journal of Graduate of Islamic Education), 2020)
The purpose of this study is to describe and analyze the teaching of Akidah Akhlak in implementing character education, where the dryness of character is a problem experienced by every nation. The research method used is qualitative with descriptive type. The method in data collection is related to the effectiveness of learning akidah morals in instilling character education. The parties that will be interviewed are the principal, curriculum assistant, Akidah Akhlak teachers, required non-PAI subject teachers, students, and other informants needed to support completeness of information. The results of this study indicate that the application of akidah akhlak learning to instill character education is integrated into the existing subjects and activity programs at MTs Darul Falah Ketapang. The Akidah Akhlak Learning which is applied by the teacher creates a habituation learning model at school and in the family environment.